Biochar as a waste management strategy for cadmium contaminated cocoa pod husk residues - Diego Armando Pinzon-Nuñez; Carlos Alberto Adarme-Duran; Luz Vargas-Fiallo; Nelson Rodriguez-Lopez; Carlos Alberto Rios-Reyes (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The role of cocoa pod husk waste in soil cadmium contamination has been largely overlooked. Hence, this study aims to provide a strategy for the management of cocoa pod husk waste when representing a pollution menace for cocoa plantations.Method Cocoa pod husks waste was subjected to composting and pyrolysis for decreasing the heavy metal content. Biochar and compost were characterized using SEM-EDS, and FTIR-ATR. Macro and micronutrients (Mg, K, Zn, Fe, Cu, Zn, Mn, and Na), and Cd were measured by atomic absorption spectroscopy (AAS). Sorption experiments and soil incubation experiments for two months were also carried out looking for an application of CPH materials in Cd sorption and remediation.Results Pyrolysis showed more effectiveness for Cd reduction in cocoa pod husk waste (90%) than composting (66%), 700 ℃ was the optimal temperature. Equilibrium isotherm experiments showed maximum Cd adsorption of 21.58 mg g-1 for Bc700 in solution. Biochar showed a small reduction of available Cd in naturally contaminated soil. Both materials have the potential to be used as organic fertilizer because of their high nutrient contents.Conclusion Biochar is an alternative to compost for the management of post-harvest cocoa wastes contaminated with Cd.